2016
DOI: 10.2298/abs150816042d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phytochemical profiling and effects of Nerium oleander extracts on the activities of murine peritoneal macrophages

Abstract: Nerium oleander is a medicinal plant. Apart from its ethnopharmacological uses, pharmacognostic studies have revealed several of its bioactivities. Previously we demonstrated that the phenolic and flavonoid rich extracts of oleander leaf, stem and root possess potent antioxidant and free radical scavenging activities. Moreover, the leaf extract actively modulates the Th1/Th2 cytokine balance and exerts anti-inflammatory activities on murine splenic lymphocytes. Therefore, the present study was designed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…The n-hexadecanoic acid or so-called palmitic acid is a fatty acid (FA) found from 1.90 to 11.52 % in the ethanolic extract of the rhizome. Compared to another finding on traditional medicinal plant, methanol extract of Nerium oleander's leaves showed higher concentration palmitic acid (52 %), lower in n-hexane extract Nerium oleander's stem (3.0 %)[47], an average (5.91 %) in supernatant mycelial extract of the fungus Aspergillus unguis and lower (1.11 %) in supernatant static extract of fungus A. unguis[66]. N-hexadecanoic acid is a potent inhibitor of phospholipase A2, hence, as an anti-inflammatory compound and for rheumatic symptoms[67].…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…The n-hexadecanoic acid or so-called palmitic acid is a fatty acid (FA) found from 1.90 to 11.52 % in the ethanolic extract of the rhizome. Compared to another finding on traditional medicinal plant, methanol extract of Nerium oleander's leaves showed higher concentration palmitic acid (52 %), lower in n-hexane extract Nerium oleander's stem (3.0 %)[47], an average (5.91 %) in supernatant mycelial extract of the fungus Aspergillus unguis and lower (1.11 %) in supernatant static extract of fungus A. unguis[66]. N-hexadecanoic acid is a potent inhibitor of phospholipase A2, hence, as an anti-inflammatory compound and for rheumatic symptoms[67].…”
contrasting
confidence: 71%
“…Clerodendrum viscosum) leaves (traditional used in Indian medicine for asthma, fever, bronchitis, skin diseases, epilepsy, inflammation, tumors, worm infestation and snake bite) also present DDMPP (4.19 %) as one of major compound detected[46], and only 4.0 % in methanolic extract of Nerium oleander stems[47], however, the concentration remained lower compared with DDMP present in the ethanolic extract of mature G. scortechinii's rhizome(19.81 -29.30 %). Benzofuran, 2,3-dihydro-(RT: 21.22±0.02), also known as coumaran was found higher at Ayer Hitam FR (18.31±4.39 %) follower by Kenaboi FR (15.96±7.31 %) and Amanjaya FR (12.63±3.53 %)(Table 6), and higher at the new sprout (25.84±3.11 %) followed by young (21.17±5.55 %), premature (8.69±2.75 %), and mature rhizome (6.82±1.71 %)(Table 5).…”
mentioning
confidence: 99%
“…[32]. Apart from the phenolic acids identified in the present study, recent studies have identified a vast array of bioactive constituents in the stem and root of oleander, several of which are well established for their potent antidiabetic activities [8, 9].…”
Section: Resultsmentioning
confidence: 96%
“…09618. Hydromethanolic (70%) extracts of stem (NOSE) and root (NORE) were prepared as described previously [8]. In brief, shade-dried and grinded 100 g of oleander stem and root were separately mixed with 1000 mL of 70% methanol and twice extracted for 12 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were analyzed using a Thermo-Scientific Trace 1300 gas chromatography instrument attached with Thermo-Scientific ISQ QD single quadrupole mass spectrophotometer following a previously standardized method. [17][18][19][20] The gas chromatography system was equipped with TG-5MS column (30 m  0.25 mm  0.25 mm). The inlet temperature was maintained at 250 C. The initial temperature was set at 60 C (solvent delay 5 minutes) with a hold of 4 minutes, followed by a ramp of 5 C/min to 290 C with a hold of 10 minutes (60-minute program).…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%